Fenomen odpowiedzialności: między nieopanowaniem a hiperkontrolą - Leontiev, Dmitry (Kultura-Społeczeństwo-Edukacja, 2019)
The paper contains a phenomenological and theoretical analysis of responsibility treated as the capacity of personal causation (taking the role of the cause of one’s actions) based upon conscious awareness and self-detachment from the immediate stream of one’s living. The manifestations of the lack of responsibility are the failure to manage one’s actions in the face of multiple forces majeures, incontinence of immediate wishes and impulses, or rigid hypercontrol over these impulses. Special sections are devoted to interrelations between responsibility and freedom, especially in the developmental aspect, and responsibility for another person.